2018
DOI: 10.3758/s13423-018-1469-y
|View full text |Cite
|
Sign up to set email alerts
|

Composing lexical versus functional adjectives: Evidence for uniformity in the left temporal lobe

Abstract: Featural information (e.g., color or shape) allows interlocutors to focus their attention on the specific items under discussion from the vast set of possibilities in the environment. Intriguingly, when they are used to modify and restrict nouns, adjectives can either carry featural information themselves (e.g., green car) or retrieve featural information from the context (e.g., somebody points at a car and claims that she has the same car or a different car). Do the processing of same/different car and green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 73 publications
1
19
1
Order By: Relevance
“…The last several decades of research on language processing has yielded many candidates for hubs of basic combinatorial processes. The combinatory role of the left anterior temporal lobe (LATL) has been characterized in a series of studies and appears to be conceptual in nature (e.g., Westerlund & Pylkkänen, 2014;Zhang & Pylkkänen, 2015;Baron & Osherson, 2011;Baron, Thompson-Schill, Weber, & Osherson, 2010;Blanco-Elorrieta & Pylkkänen, 2016;Poortman & Pylkkänen, 2016;Zhang & Pylkkänen, 2018a;Zhang & Pylkkänen, 2018b;Kim & Pylkkänen, 2019), a finding also supported by studies of language deficits e.g., (Lukic, et al, 2021;Mesulam, et al, 2019;Mesulam, Thompson, Weintraub, & Rogalski, 2015;Wilson, et al, 2014). At the same time though, the LATL also correlates with syntactic processing steps during narrative comprehension (Humphries, Love, Swinney, & Hickok, 2005;Brennan, Stabler, Van Wagenen, Luh, & Hale, 2016), though the extent to which these results may reflect semantic processing is unclear.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The last several decades of research on language processing has yielded many candidates for hubs of basic combinatorial processes. The combinatory role of the left anterior temporal lobe (LATL) has been characterized in a series of studies and appears to be conceptual in nature (e.g., Westerlund & Pylkkänen, 2014;Zhang & Pylkkänen, 2015;Baron & Osherson, 2011;Baron, Thompson-Schill, Weber, & Osherson, 2010;Blanco-Elorrieta & Pylkkänen, 2016;Poortman & Pylkkänen, 2016;Zhang & Pylkkänen, 2018a;Zhang & Pylkkänen, 2018b;Kim & Pylkkänen, 2019), a finding also supported by studies of language deficits e.g., (Lukic, et al, 2021;Mesulam, et al, 2019;Mesulam, Thompson, Weintraub, & Rogalski, 2015;Wilson, et al, 2014). At the same time though, the LATL also correlates with syntactic processing steps during narrative comprehension (Humphries, Love, Swinney, & Hickok, 2005;Brennan, Stabler, Van Wagenen, Luh, & Hale, 2016), though the extent to which these results may reflect semantic processing is unclear.…”
Section: Introductionmentioning
confidence: 96%
“…However, if the process of conceptual combination is separate from or does not rely on syntactic parsing steps, then we expect both pleasantly sunny and pleasant sunny to show similarly greater LATL activation compared to a non-combinatory control (Figure 1.D). As the majority of past studies looking at LATL conceptual combination has focused on adjectival modification of nouns (e.g., Poortman & Pylkkänen, 2016;Zhang & Pylkkänen, 2018a;Blanco-Elorietta et al, 2018), we also introduced a noun manipulation into the experiment. Rather than using morphological cues to manipulate whether direct syntactic composition occurs, we created stimuli where syntactic composition between two words is not impossible, but rather closure of the phrase as a whole is blocked due to temporary ungrammaticality.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the study presented here represents the first effort to study semantic representations of adjective-noun phrases using the fine time resolution offered by magnetoencephalography (MEG). This is in contrast to previous work interested in the brain areas that respond to stimuli requiring composition, or differing types of composition (Bemis & Pylkkänen, 2011;Flick et al, 2018;Westerlund & Pylkkänen, 2014;Zhang & Pylkkänen, 2018). To study adjective-noun phrases in the brain, we traced the flow of information through time and brain space.…”
Section: Introductionmentioning
confidence: 99%
“…Since only two studies observed the LATL composition without color adjectives and one study (ours) does not find evidence for such effect, it is possible that the LATL composition effect is only robustly observed for adjective-noun phrases with color 20 We are not certain that the materials in Standard Arabic used by Westerlund and Pylkkänen (2015) did not include color adjectives; the effect reported by Blanco-Elorrieta and Pylkkänen (2016) for complex numbers was much later than the expected LATL composition effect; finally, Zhang and Pylkkänen (2018) and (2019) report significant effects for other types of adjectives and for adverbs correspondingly, but in both cases only when analyzed separately and without multiple comparisons correction reported.…”
Section: Potential Reasons For the Failure To Observe The Latl Composmentioning
confidence: 71%
“… 20 We are not certain that the materials in Standard Arabic used by Westerlund and Pylkkänen (2015) did not include color adjectives; the effect reported by Blanco-Elorrieta and Pylkkänen (2016) for complex numbers was much later than the expected LATL composition effect; finally, Zhang and Pylkkänen (2018) and (2019) report significant effects for other types of adjectives and for adverbs correspondingly, but in both cases only when analyzed separately and without multiple comparisons correction reported.…”
mentioning
confidence: 98%